Kinerja Guru: Kunci Sukses Hasil Belajar Siswa di SMK Swasta HKBP Lintongnihuta - Lincaria Sianturi; Erika Christine Panggabean; Tetti Manullang; Abai Manupak Tambunan; Betty As Pakpahan (Institut Nalanda, 2024)
The aim of this research is to analyze and determine the influence of teacher performance on student learning outcomes at the HKBP Lintongnihuta Private Vocational School for the 2023/2024 Academic Year. The method used in this research is a quantitative method with an initial statistical statistical approach. The population is all students of the HKBP Liintongniihuta Private Vocational School for the 2023/2024 academic year, totaling 245 people and a sample of 71 was determined using random sampling techniques. Data was collected using a closed questionnaire with 34 items. The results of data analysis show that teacher performance has a positive and significant influence on student learning outcomes at the HKBP Liintongniihuta Private Vocational School for the 2023/2024 Academic Year, proven through the following data analysis: 1) Test the analysis requirements: a) positive relationship test obtained by the value rxy = 0.550 > rtable(=0.05,n=71) = 0.235, thus it is known that there is a positive relationship between variable =n-2=69)= 2,000, thus there is a significant relationship between variable b) Regression coefficient of determination test (r2) = 30.2%. 3) Test the hypothesis using the F test to obtain Fcount > Ftable, namely 29.894 > 4.00. Thus Ha is accepted and H0 is rejected. So it can be concluded that teacher performance has a positive and significant influence on student learning outcomes at the HKBP Lintongnihuta Private Vocational School for the 2023/2024 Academic Year.